Neutral glycolipids of atherosclerotic plaques and unaffected human aorta tissue - PROKAZOVA, Nina V.; MUKHIN, Dmitry N.; OREKHOV, Alexander N.; GLADKAYA, Elena M.; VASILEVSKAYA, Valentina V.; MIKHAILENKO, Irina A.; SADOVSKAYA, Valentina L.; BUSHUEV, Valery N.; BERGELSON, Lev D. (European journal of biochemistry, 1989)
The composition, structure and localization of neutral glycosphingolipids of human aorta taken from subjects who had died after myocardial infarction were studied. Individual glycosphingolipids were purified by high‐performance liquid chromatography and were characterized on the basis of their chromatographic mobility, carbohydrate composition, methylation analysis and by 1H‐NMR spectroscopy. The main aortic glycosphingolipids were identified as glucosylceramide, lactosylceramide, globotriaosylceramide and globotetraosylceramide. Significant differences in the neutral glycosphingolipid composition of intima and media were detected. The neutral glycosphingolipid profile of medial plaques resembled that of unaffected media; however, significant differences were detected between intimal plaques and unaffected intima. Whereas the latter contained trihexosylceramide and globoside as the only neutral glycolipids, the intimal plaque glycolipids consisted mainly of glucosylceramide and also contained appreciable amounts of lactosylceramide which were completely absent in the unaffected intima. In comparison to intimal plaques, unaffected intima is characterized by a much higher content of cerebrosides terminating by β‐galactosyl residues which are known to interact with growth factors and other external stimuli. It thus seems possible that the proliferative activity of smooth muscle cells in atherosclerotic diseases is to some extent associated with their neutral glycolipid profile.